2014
DOI: 10.1097/prs.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Whole-Vault Cranioplasty versus Strip Craniectomy on Long-Term Neuropsychological Outcomes in Sagittal Craniosynostosis

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 50 publications
2
99
1
Order By: Relevance
“…In a multicenter study, Hashim et al found that patients who underwent whole-vault cranioplasty attained higher intelligence quotient and achievement scores than those treated with strip craniectomy. 8 It is unclear if the conclusions drawn by these authors are truly applicable to our patients. Our technique is notably different in that our patients did not receive suture constriction in the anterior-posterior dimension and instead received postoperative helmeting.…”
Section: Limitationsmentioning
confidence: 71%
“…In a multicenter study, Hashim et al found that patients who underwent whole-vault cranioplasty attained higher intelligence quotient and achievement scores than those treated with strip craniectomy. 8 It is unclear if the conclusions drawn by these authors are truly applicable to our patients. Our technique is notably different in that our patients did not receive suture constriction in the anterior-posterior dimension and instead received postoperative helmeting.…”
Section: Limitationsmentioning
confidence: 71%
“…This focus on cosmetic outcomes has diverted attention from the cognitive changes that occur after sagittal synostosis surgery. A multiinstitutional evaluation 9 of the minimally invasive endoscopic strip craniectomy compared with cranial vault repair found the latter to have better long-term cognitive testing outcomes despite the increased morbidity and later age of operation. This brings up several important considerations when treating sagittal craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 There is an increasing body of evidence to suggest that from a neurocognitive standpoint, outcomes are improved when intervention occurs early (less than 6 months of age) and with either CVR or active expansion after suturectomy. 9 However, a large procedure at a younger age poses considerable risks, including prolonged operative time, increased blood loss, and longer hospital stays.…”
mentioning
confidence: 99%
“…However, age at surgery is potentially confounded with numerous other variables that might be associated with development, such as family SES, initial severity, surgical approach used, and duration. For example, surgeries at younger ages may well provide optimal benefits in terms of earlier suture release, 20,39 but less mature brains may be more susceptible to the neurotoxicity associated with anesthesia exposure. 38 In our own work, we have found little association between surgery age and neurodevelopmental outcomes measured both in infancy 45 and at school age 12 when controlling for potential confounding variables such as maternal IQ, SES, and involved suture.…”
Section: Discussionmentioning
confidence: 99%